EXAMINATION OF PLANS IN URBAN REDEVELOPMENT AREAS IN ISTANBUL REGARDING SOCIAL INFRASTRUCTURE - Sakarya, Adem; Bektas, Yasin (MIDDLE EAST TECHNICAL UNIV, 2024)
The phenomenon of urban redevelopment has had an important place in urban policies in Turkey since the 2000s. Urban redevelopment, which was mostly aimed at transforming squatter settlements at the end of the 1980s, and later expanded to transform at-risk areas, also aims to create healthy and safe living environments in accordance with the norms and standards of science and art. In this study, urban redevelopment is analyzed in terms of social facilities. The study focuses on at-risk areas in & Idot;stanbul. & Idot;stanbul has 68 at-risk areas, and 51 have new urban plans after the urban redevelopment declaration. In analyzing the change in social facilities in a comprehensive framework, these plans for 51 at-risk areas are compared to the current situation of the area. Educational facilities, open and green areas, health facilities, social and cultural facilities, and religious facilities that are all defined in Regulation for the Preparation of Spatial Plans are taken as social facilities in the study. Moreover, the change in population, density, and land use texture are analyzed. In conclusion, the social facilities were increased as area; but for the social facilities area per person, the increase is limited because of planning high population and density in at-risk areas. For most at-risk areas, the population and density increased because of the creation of financial sources. In land use, the transformation of industrial areas is the main concern, and the one-type zones are transformed into mixed-used as housing + commercial + tourism. The findings show that urban redevelopment plans are inconsistent with the population forecasts for the city as a whole in upper-scale plans. Additionally, the findings indicate that the plans for at-risk areas and reserve areas need to be interrelated. The relationship between at-risk areas and reserve area plans shows an ideal process for future implementations to increase the social infrastructure areas in dense urban areas.
Keywords: Urban redevelopment; social facilities; density; urban densification; Istanbul; HOUSING POLICY; WELFARE-STATE; CITIES; TRANSFORMATION; DENSIFICATION; REGENERATION; GENTRIFICATION; GLOBALIZATION; NEOLIBERALISM; URBANIZATION; Architecture